PENGARUH KOMPETENSI, INDEPENDENSI DAN MOTIVASI TERHADAP KUALITAS AUDIT (Studi Empiris pada Kantor Wilayah DJBC Jawa Barat dan Kantor Wilayah DJBC Jawa Tengah dan D.I. Yogyakarta) - Ilham Effendie, 0835030535; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
The Purpose of this reseach is to empirically analyse the influence of Competency, Independency and motivacy on quality of audit especially in the customs and excise auditor working in Regional office of West Java and regional office of Central Java and Yogyakarta. The Population of this research are all customs and excise auditors havebeen working in the Regional office of West Java and the regional office of Central Java and Yogyakarta. Sampling was conducted using sencus method. Primary data collection method used is multiple regression model.The result showed that competency and motivacy have a position impact on audit quality. And independency daesnât have aposition impact on audit quality.Keywords: Competency, independency, motivation, audit quality.